Carpal agenesis in a domestic short haired cat - Gemmill, T. J.; Clarke, S. P.; Carmichael, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Carpal bone agenesis and bifurcation of the distal radial physis were diagnosed in a domestic short haired cat. Until skeletal maturity, the animal was treated conservatively, and the condition was then treated by antebrachiometacarpal arthrodesis using dorsal stacked 1.5-mm veterinary cuttable plates and a supplementary cross pin. Following the operation, the cat gained good use of the affected limb. To the authors’ knowledge, this is the first report of carpal agenesis and its successful treatment in the veterinary literature.
Keywords: Agenesis; arthrodesis; carpus; cat